The Role of Taboos in the Protection and Recovery of Sea Turtles - Alexander, LoriKim; Agyekumhene, Andrews; Allman, Phil (Frontiers in Marine Science, 2017)
Despite increased efforts from government agencies, scientists, and non-government organizations over the past few decades, anthropogenic sources of sea turtle mortality continue to threaten the survivorship of sea turtle species around the globe. More recent efforts to engage local people with community-based sea turtle conservation programs have been based primarily on economic incentives and less on cultural and social traditions. But there is growing evidence that informal institutions such as taboos can be extremely effective at promoting wildlife conservation. Ghana is a culturally diverse country where local traditions have shown to improve protection for primates, crocodiles, and many bird species. This study explores the presence of a sea turtle taboo in fishing communities to demonstrate that traditional practices make residents more receptive to sea turtle conservation and more willing to follow government regulations. Fishers in the communities that are aware of the taboo are also more willing to adjust fishing methods to better protect sea turtles. The traditional taboo and national laws appear to be working synergistically to enhance sea turtle conservation in some regions of Ghana. This paper extends the argument that sea turtle conservation strategies succeed when the cultural and social traditions of local communities are integrated with management activities.